Competitive Strategy to Improve Performance in Aviation Education and Training Institutions - Rozikin, Imam; Suharno, FA Suharno; Felina, Felina (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
This research aims to determine the Formulation of Competitive Strategy, Competitive Matching Stage Strategy, Competitive Decision Stage Strategy. The research method uses a quantitative descriptive approach that describes events in the research field. Data collection techniques: direct in-depth interviews with resource persons, observation through observing phenomena at the research location. Study documentation through archives in the education and training office, official records of the results of plenary meetings. Conclusions through analysis are carried out through stages, namely the data input stage with the IFE, EFE, CPM matrices, then the matching stage with the IE, Grand Strategy, SWOT matrices, then the decision stage using the Quality Strategy Planning matrix. Once the selected strategy is known, its implementation is carried out by creating a short-term and long-term logical framework. The conclusion from the strategic analysis carried out is that the company's position is in quadrant I with an aggressive strategy with the chosen strategy being market penetration by carrying out intensive and wider promotions by optimally utilizing information and communication technology.